Sources, transport and deposition of terrestrial organic material: A case study from southwestern Africa. (1st October 2016) - Herrmann, Nicole; Boom, Arnoud; Carr, Andrew S.; Chase, Brian M.; Granger, Robyn; Hahn, Annette; Zabel, Matthias; Schefuß, Enno
Abstract: Southwestern Africa's coastal marine mudbelt, a prominent Holocene sediment package, provides a valuable archive for reconstructing terrestrial palaeoclimates on the adjacent continent. While the origin of terrestrial inorganic material has been intensively studied, the sources of terrigenous organic material deposited in the mudbelt are yet unclear. In this study, plant wax derived n -alkanes and their compound-specific δ 13 C in soils, flood deposits and suspension loads from regional fluvial systems and marine sediments are analysed to characterize the origin of terrestrial organic material in the southwest African mudbelt. Soils from different biomes in the catchments of the Orange River and small west coast rivers show on average distinct n -alkane distributions and compound-specific δ 13 C values reflecting biome-specific vegetation types, most notably the winter rainfall associated Fynbos Biome of the southwestern Cape. In the fluvial sediment samples from the Orange River, changes in the n -alkane distributions and compound-specific δ 13 C compositions reveal an overprint by local vegetation along the river's course. The smaller west coast rivers show distinct signals, reflecting their small catchment areas and particular vegetation communities. Marine surface sediments spanning a transect from the northern mudbelt (29°S) to St. Helena Bay (33°S) reveal subtle, but spatially coherent, changes in n -alkane distributions and compound-specific δ 13 C, indicating the influence of Orange River sediments in the northern mudbelt, the increasing importance of terrigenous input from the adjacent western coastal biomes in the central mudbelt, and contributions from the Fynbos Biome to the southern mudbelt. These findings indicate the different sources of terrestrial organic material deposited in the mudbelt, and highlight the potential the mudbelt has to preserve evidence of environmental change from the adjacent continent. Highlights: A source-to-sink approach for terrestrial organic material in South Africa. Plant wax derived n -alkanes and its compound specific δ 13 C were used. De-coupling of organic and inorganic source signals transported by the Orange River. Fluvially-transported overprint of terrestrial organic material by local vegetation. Different sources of terrestrial organic material in southwest African mudbelt.